Biodiesel Production From Bintanggur Oil (Callophyllum inophyllum L.) Using Calsium Oxide (CaO) Catalyst - Sutapa, I Wayan; Rosmawaty, Rosmawaty; Samual, Ismah (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2013)
The research of the biodiesel from bintanggur oil (Calophyllum inophyllum L.) using calsium oxide (CaO) catalyst had been done. In this study, a two-step process was used to produce biodiesel from bintanggur oil. Initially by esterification process using H2SO4 1.25% catalyst by weight of oil and methanol with a molar ratio of 1:9 and continued by transesterification process with 1:12 (oil : methanol) with the catalyst 8 wt% CaO. The esterification and the transesterification process carried out of 2 hours and 7 nespectively at a 65 °C. The synthesis of biodiesel was analyzed by FT-IR spectrophotometer. The conversion of biodiesel is 44.49%. The biodiesels properties were caracterized by ASTM method. Results of biodiesels properties there are specific gravity of 0.8878 g/cm3, viscosity kinematic 5.572 cSt, flash point 176.5 °C, pour point 9 °C, cooper strip corrosion 1b, and Conradson carbon residue 2.469%.